ANALISIS RISIKO PAJANAN NH3 DAN H2S TERHADAP GANGGUAN PERNAPASAN PADA PENDUDUK DI SEKITAR TEMPAT PEMBUANGAN AKHIR SAMPAH BUKIT PINANG SAMARINDA - Ade Rahmat Firdaus (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2016)
The air pollution in the garbage dump gave the bad effect for the environmental health , NH3, H2S and the other polluted gases were the causes of air pollution that could give the bad effect for health, especially respiratory disorders. The garbage dump of bukit pinang was located in samarinda and still used open dumping method that could cause environmental pollution. Research design used cross sectional approach. The sample of NH3 and H2S was taken at 3 points and there were 34 respondents that were chosen using purposive sampling. Data collection included in the measurement of NH3 and H2S, interview, and observation of respiratory disorders. Data analysis used t-independent test with 95% of confidence level.Result of the study showed that the concentration of NH3 and H2S at garbage dump of Bukit Pinang at sample points I, II, and III was still under quality standard. Result of T - Independent showed that there was relationship among concentration of NH3 (?-value= 0,005), concentration H2S (?-value=0,042), exposure period of NH3 and H2S (?-value=0,000), and Risk Quotient NH3 (?-value=0,000), H2S (?-value=0,000) with the respiratory disorders of the people around the garbage dump of  bukit pinang. Result of Mann-Whitney test showed that there was no relationship between exposure frequency of NH3 and H2S (?-value=0,284) with the respiratory disorders of the people around the garbage dump of bukit pinang